Publishing research data: Contextualizing the main steps and elements involved in the process - Dias, Guilherme Ataíde [UNESP] (2020)
The use and reuse of research data are important and necessary actions in the current context of scientific practice. For this reason, the datasets produced during the research initiatives need to be published to be more easily accessed by the entire scientific community. However, publishing data does not mean merely making it available in a repository, but comprises a series of steps that must be considered so that they can be effectively used. Thus, this work has as main objective to discuss the process of publishing research datasets in the context of science. This is a descriptive and qualitative investigation, which makes use of bibliographic research. As results, elements involved in the process of publishing research data and discussions are presented, covering the stages of publication of datasets, relating to the deposit, description, identifier assignment and review, steps that involve the core of the publication process.